2012
DOI: 10.5539/jas.v4n12p48
|View full text |Cite
|
Sign up to set email alerts
|

Effects Different Levels of Nanoparticles Chromium Picolinate Supplementation on Growth Performance, Mineral Retention, and Immune Responses in Broiler Chickens

Abstract: This study was conducted to investigate the effects of different levels nanoparticles of chromium picolinate (NanoCrPic) on the performance, immune responses, mineral retention, and tissues accumulation of chickens. A total of 180 broilers were randomly allocated into 0 (control), 500 ppb (µg kg -1 ) Cr and 3000 ppb Cr groups with 6 replicates (10 birds/pen) for a 35-day experiment, the Cr is nanoparticles of chromium picolinate (NanoCrPic). In addition, 36 birds were used for metabolic experimental investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…In addition, Cr has been shown that supplemental chromium led to increased Cr and Zn in serum, liver, kidney and longissimus muscle of laying hens and Japanese quails (Sahin et al, 2002a;Sahin et al, 2002b), but Fe concentrations were not affected in Japanese quails. Our previous study also indicated that NanoCrPic supplementation in broilers diet increased the concentration of Cr and Ca in the liver (Sirirat et al, 2012). Those reports were agreed with our results.…”
Section: The Effects Of Various Levels Of Nanocrpic On the Liver And supporting
confidence: 82%
See 1 more Smart Citation
“…In addition, Cr has been shown that supplemental chromium led to increased Cr and Zn in serum, liver, kidney and longissimus muscle of laying hens and Japanese quails (Sahin et al, 2002a;Sahin et al, 2002b), but Fe concentrations were not affected in Japanese quails. Our previous study also indicated that NanoCrPic supplementation in broilers diet increased the concentration of Cr and Ca in the liver (Sirirat et al, 2012). Those reports were agreed with our results.…”
Section: The Effects Of Various Levels Of Nanocrpic On the Liver And supporting
confidence: 82%
“…Our results are in agreement with the results of Sahin and Sahin (2002), who reported that the retention of Zn was improved by supplemental Cr and ascorbic acid. In our previous study with broiler also indicated that supplemental NanoCrPic improved the retention of Zn (Sirirat et al, 2012), which may be owing to the Zn excretion being reduced in NanoCrPic group. Amatya et al (2004) also reported that supplemental Cr had effect on the retention of Zn and Mn in broilers.…”
Section: The Effects Of Various Levels Of Nanocrpic On the Minerals Rmentioning
confidence: 99%
“…They however observed no statistically significant differences (p>0.05) on monophil, esonophil and basophil percentages between treatment groups supplemented with vitamin E and control groups. Sirirat et al (2012), in a study conducted to investigate the effects of different levels nanoparticles of chromium picolinate (NanoCrPic) on the performance, immune responses, mineral retention, and tissues accumulation of chickens reported significant increase in lymphocytes (p<0.0004) as the level of Cr supplementation increased to 3000ppb. Zha et al (2008) observed lympho proliferative response in rats feed supplementary Cr of 150, 300 and 450 ppb.…”
Section: Effect On Hematological Characteristicsmentioning
confidence: 99%
“…Recently, nanotechnology has rapidly been developing different scientific areas and nanoscale of materials has interested extention because nano-formulation particulates exhibit novel distinguishing quality such as a size, shape, large surface area, high surface activity, high catalytic efficiency and strong adsorbing ability [21] . Limited published data in various experimental conditions implicated higher absorption and bioavailability of chromium nanoparticles [22][23][24] . Previous researches have shown that chromium nanoparticles had beneficial properties on growth performance, body composition, as well as augmented tissue concentrations of Cr in selected muscles [25] and serum [24] .…”
Section: Introductionmentioning
confidence: 99%